Mills hemiparetic or hemiplegic variant of amyotrophic lateral sclerosis - Barua, Amit R.; Borah, Nomal C.; Barthakur, Mausumi; Choudhury, Dhruba J.; Sharma, Jai P.; Kemprai, Pari (International Journal of Research in Medical Sciences, 2020)
Mills hemiplegic variant of Amyotrophic lateral sclerosis (ALS) is a gradually progressive, spastic ascending or descending hemiparesis or hemiplegia without any sensory involvement. Authors presented a 47 years old female with history of gradually progressive left sided wasting of muscles including the tongue, left hemiparesis along with dysarthria and fasciculation’s of tongue and left sided muscles with left sided cortico-spinal tract signs of 2 years duration. There were no sensory as well as bowel bladder involvement. Her cognition was intact. Relevant blood and CSF examinations were within normal limit. MRI Brain and whole spine were unremarkable. Nerve conduction study was essentially normal. Electromyography(EMG) showed chronic denervation potentials which is in accordance to Revised El Escorial criteria, 2015 for the diagnosis of this extremely uncommon entity- Mills hemiplegic variant of ALS. The major challenge in diagnosis of this disease entity is to exclude other diseases/disorders that may mimic its symptomatology.